2016
DOI: 10.1055/s-0035-1570741
|View full text |Cite
|
Sign up to set email alerts
|

Volar Central Portal in Wrist Arthroscopy

Abstract: Background?Nowadays, the wrist is not limited to a dorsal visualization; the joint can be thought of as a ?box,? which can be visualized from almost every perspective. The purpose of this study was to describe a new volar central portal for the wrist, following three principles: a single incision that allows access to both the radiocarpal and midcarpal joints, centered on the lunate, with the volar structures at risk protected not only by retractors, but also by tendons. Description of Technique?The incision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Access to the midcarpal joint at the volar level requires an approach with dissection and protection of the major neurovascular structures. 2 Viegas 3 described the triquetrohamate (TH) portal, which enters the midcarpal joint at the level of the TH joint ulnar to the extensor carpi ulnaris (ECU) tendon. The entry site is ulnar and distal to the MCU and approximately 1 cm distal to the 6R accessory portal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to the midcarpal joint at the volar level requires an approach with dissection and protection of the major neurovascular structures. 2 Viegas 3 described the triquetrohamate (TH) portal, which enters the midcarpal joint at the level of the TH joint ulnar to the extensor carpi ulnaris (ECU) tendon. The entry site is ulnar and distal to the MCU and approximately 1 cm distal to the 6R accessory portal.…”
Section: Discussionmentioning
confidence: 99%
“…1 Advances in wrist arthroscopy and the emergence of new surgical techniques and implants have created the need to design new portals to facilitate the implementation of these techniques. 2 The development of surgical techniques to repair acute and chronic lesions of the intercarpal scapholunate ligament (SLL) and lunotriquetral ligament (LTL) prompted us to design a new dorsal portal at the midcarpal level and ulnar to the midcarpal ulnar portal that would facilitate the placement of implants and provide us with a third working portal in the midcarpal joint, avoiding damage to major structures. The medial triquetrohamate (MTH) portal allows better placement of the implants, with a better angle of attack and gives us a second working portal at the midcarpal level.…”
mentioning
confidence: 99%
“…He even emphasized that with the use of an accessory volar portal, correction of the scaphoid deformity is achieved in a more effective, safe, and predictable way. Corella et al 27 described a volar central midcarpal portal that offers good visualization of the volar scaphoid and could also be useful for nonunion instrumentation and grafting. Zemirline et al 15 showed a technique where the volar portal is used for the insertion of a cannula that facilitates the placement of the bone graft removed from the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for this portal has been explained in detail before. 4 The volar central portal is formed via a 1.5-cm longitudinal incision following the longitudinal axis of the third intermetacarpal space beginning in the distal wrist crease. Through blunt dissection, all the flexor superficialis tendons and the second and third flexor profundus tendons are retracted toward the radial side, while the fourth and fifth flexor profundus tendons are retracted toward the ulnar side.…”
Section: Surgical Techniquementioning
confidence: 99%